Effects of a soccer season on anthropometric characteristics and physical fitness in elite young soccer players - Hammami, M. A.; Abderrahmane, A. B.; Nebigh, A.; Le Moal, E.; Ounis, O. B.; Tabka, Z.; Zouhal, H. (Journal of Sports Sciences, 2013)
The aim of this study was to evaluate the effect of a soccer-training season on the anthropometric and performance characteristics of elite youth soccer players.